Bamboo Scrimbers Prepared from Dendrocalamus membranaceus: A Study on its Suitability for Structural Applications - Dhyani, Nirmal; Khali, D.P.; Rawat, Rakesh Singh (Indian Forester, 2024)
Bamboo is a versatile and sustainable material that is increasingly being used to replace timber and timber-based products. This study focuses on bamboo scrimber prepared from Dendrocalmus membranaceus. The study assesses the effect of various manufacturing pressure levels (ranging from 21.0 to 31.5 kg/cmÂ²) on physical properties, including moisture content, density, water absorption, and general swelling, as well as mechanical properties such as Modulus of Rupture (MOR), Modulus of Elasticity (MOE), hardness, and compression parallel to the grain of the scrimber prepared using Phenol formaldehyde (PF) adhesive. The results demonstrated a clear positive correlation between increasing pressure and the enhancement of both physical and mechanical attributes of the bamboo scrimber. This highlights its potential as a sustainable and effective alternative to conventional wood. The research underscores the feasibility of Dendrocalmus membranaceus bamboo scrimberas a credible option for diverse construction applications. Despite varying outcomes due to pressure differentials, the overall findings emphasize the versatility of Dendrocalmus membranaceus-derived bamboo scrimbers. These materials possess ecological sustainability and exhibit high-performance characteristics suitable for applications ranging from furniture to construction and beyond. The study suggests the potential for utilizing lower specific pressures in semi-structural contexts, while also proposing further investigations involving alternative adhesives and pressure levels to foster an economically sustainable approach to production.